(untitled) (Journal of Veterinary Medicine and Animal Production, 2021)
The aim of this study was to provide information on the influence of stunning voltage on broiler carcass quality and to investigate the effect of year season (winter, summer and autumn) on the percentage of causes of carcasses condemnation in nine poultry slaughterhouses located in Khartoum state. The data were collected by the Veterinary Inspection Services of the Ministry of Agriculture and Animal Rescores and Irrigation, in 2016. The commercial poultry slaughterhouses use different stunning voltages. According to the stunning voltage used the treatments were divided into three groups, Group 1: 25mA, Group 2: 35mA and Group3: 45mA. The influence of electrical stunning voltage on apparent carcasses defects (breast muscle hemorrhage, red wing tips, broken bone, and bleeding) was studied. Also the effect of year season on causes of carcasses condemnation was recorded. Complete randomized design with factorial arrangement was used, each treatment group was replicated 3 times. The collected data were subjected to analysis of variance (ANOVA). The results revealed that high stunning voltage at 45 mA significantly (P ≤ 0.05) reduced the breast muscle hemorrhages, red wing tips, bleeding and resulted in a better carcass quality compared to other applied voltages (25mA, and 35mA). The different seasons were found to have significant (P ≤ 0.05) effects on percentage of causes carcasses condemnations. The percentage of carcass condemned with breast muscle hemorrhage and red wing tips were significantly (P ≤ 0.05) lower in winter compared to summer and autumn. The incidence of condemned carcasses was significantly (P ≤ 0.05) high (0.50%) in summer and autumn (0.45%) while significantly (P ≤ 0.05) lower percentage values were recorded in winter (0.13%). The study concluded that carcasses defects were reduced when (45mA) stunning voltage versus 25- 35mA was used and the lowest percentage of carcasses condemned were observed during winter season. The usage of high stunning voltage is recommended for better carcass quality.